2002
DOI: 10.1093/aje/155.8.719
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Anomalies among the Offspring of Women with Gestational Diabetes

Abstract: A limited body of data over the past 35 years has suggested that autoimmunity may be responsible for some cases of aneuploidy. The role of diabetes mellitus in the etiology of chromosomal anomalies has been infrequently studied. This study was designed to compare the prevalence of chromosome abnormalities among the offspring of women with gestational diabetes and the offspring of women without it. The authors used data from 7,332 women who underwent amniocentesis in a prospective study of pregnancy outcome (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The finding that HGC results in in vitro DNA damage and causes chromosomal abnormality in ECs proposes a mechanism of diabetes‐induced vascular complications. Moore et al previously showed underlying biochemical changes and chromosomal defects in the offspring of women for gestational diabetes . Here, it was deciphered that HGC contributed to an elevated level of the SFAs, particularly at 72 hours, whereas the levels of the PUFAs decreased in response to 30mM of glucose concentration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The finding that HGC results in in vitro DNA damage and causes chromosomal abnormality in ECs proposes a mechanism of diabetes‐induced vascular complications. Moore et al previously showed underlying biochemical changes and chromosomal defects in the offspring of women for gestational diabetes . Here, it was deciphered that HGC contributed to an elevated level of the SFAs, particularly at 72 hours, whereas the levels of the PUFAs decreased in response to 30mM of glucose concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Moore et al previously showed underlying biochemical changes and chromosomal defects in the offspring of women for gestational diabetes. 37 Here, it was deciphered that HGC contributed to an elevated level of the SFAs, particularly at 72 hours, whereas the levels of the PUFAs decreased in response to 30mM of glucose concentration. Some authors have claimed the critical role of stearoyl-CoA desaturase in the conversion of SFAs into PUFAs under different conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Investigations into the relationship between triploidy and maternal age either found no association [Uchida and Freeman, 1985;Rochon and Vekemans, 1990;Ford et al, 1996] or a decreased risk of triploidy with increasing maternal age [Neuber et al, 1993]. Triploidy risk does not appear to be influenced by maternal diabetes [Moore et al, 2002], but may be related to delayed fertilization associated with prolonged menstrual cycles or the cessation of oral contraceptive use [Niebuhr, 1974]. Cases of triploidy has been reported among embryos and fetuses found in recurrent miscarriages [Carp et al, 2001] and resulting from in vitro fertilization [Ulmer et al, 1985;Angell et al, 1986].…”
mentioning
confidence: 99%
“…The study of the role of diabetes mellitus in the etiology of chromosomal aneuploidies has shown that offspring of mothers with gestational diabetes have a crude prevalence of chromosomal defects that are twice as high as those seen in offspring of women without gestational diabetes mellitus (1,5). This has brought forth the theory that infants of mothers with gestational diabetes mellitus may have underlying biochemical changes that induce chromosomal non-disjunction and aneuploidies.…”
Section: Discussionmentioning
confidence: 99%